We can set up a system of equations based on the information given. Let's define:
- \( x \) = Jenny's current age
- \( y \) = Bill's current age
From the problem, we have the following two equations:
-
The combined age:
\[ x + y = 50 \] -
The age difference from sixteen years ago:
Sixteen years ago, Jenny's age was \( x - 16 \) and Bill's age was \( y - 16 \). It is given that at that time, Jenny was twice as old as Bill: \[ x - 16 = 2(y - 16) \]
Now, we can simplify the second equation:
\[ x - 16 = 2y - 32 \] \[ x = 2y - 32 + 16 \] \[ x = 2y - 16 \]
Now we have a system of two equations:
- \( x + y = 50 \)
- \( x = 2y - 16 \)
We can substitute the second equation into the first equation:
\[ (2y - 16) + y = 50 \] \[ 3y - 16 = 50 \] \[ 3y = 66 \] \[ y = 22 \]
Now that we have \( y \), we can find \( x \) using the first equation:
\[ x + 22 = 50 \] \[ x = 50 - 22 \] \[ x = 28 \]
Thus, Jenny's current age is \( 28 \) and Bill's current age is \( 22 \).
To summarize:
- Jenny's age, \( x = 28 \)
- Bill's age, \( y = 22 \)
You can check the conditions:
- Combined age: \( 28 + 22 = 50 \) (correct)
- Sixteen years ago, Jenny was \( 28 - 16 = 12 \) and Bill was \( 22 - 16 = 6 \). Indeed, \( 12 \) is twice \( 6 \) (correct).
So the solution is verified.